Evaluation of the Nutrition Installation Information System at RS Melati Tangerang Using the CIPP Model: Evaluasi Sistem Informasi Instalasi Gizi RS Melati Tangerang Menggunakan Model CIPP - Nafi’a, Zidni Ilma; Amallia, Ade (Politeknik Assalaam Surakarta, 2025)
The implementation of the nutrition installation information system at RS Melati Tangerang still encounters several obstacles. This research aims to evaluate the nutritional installation information system at RS Melati Tangerang using the CIPP model. This type of research is a qualitative method with a case study approach. Evaluation using the CIPP model (Context, Input, Process and Product). The 5 informants included the Head of the Nutrition Installation (1 person), the Nutritionist (1 person), the Cook (1 person), and the Waiter (2 people). Data collection techniques through interviews and observation. The data that has been collected is then analyzed through stages: data reduction, data presentation and drawing conclusions. The research results show that the problems with the nutrition installation information system at RS Melati Tangerang include: programmer limitations, not all features in the system can be used, there are parts between units that are not yet integrated in the system and do not facilitate the overall service and weak monitoring. The information system for the nutrition installation at RS Melati Tangerang received a positive response, however problems were found that had an impact on service integration. It is necessary to fulfill resource needs, build an integrated system and strengthen monitoring and evaluation.